Alteration of Consumption Habits in Turkey Over Time - Mahmut Zeki Akarsu (Research in Social Sciences and Technology, 2021)
Simon Kuznets and John Maynard Keynes did research on the subject of propensity to consume. Kuznets asserted that people do not alter their consumption/saving ratio and spend more when they have more disposable income. Keynes alleged that when disposable income increases, the rate of saving also increases over time because people tend to keep their consumption habits steady. Namely, the consumption/saving ratio of households or individuals tends to decrease as disposable income goes up. And in this study, the Keynesian consumption function is investigated in the Turkish economy. The result of this research might give insight into the future of the consumption/saving ratio in Turkey. In the study, the ARDL econometric model is operated with data from the Turkish Statistical Institute. The result of the study is that people change their consumption habits with the increase of disposable income. As a result, the consumption level has been slowing down, and the propensity to consume diminishes. That proves that the Keynesian consumption function holds in Turkey.